KEBIJAKAN BANK BTN KANTOR CABANG SOLO MEMBERIKAN RELAKSASI KREDIT BAGI DEBITUR SAAT MASA PANDEMI COVID-19 (Studi Kasus di Bank Tabungan Negara Kantor Cabang Solo) - Deassy Prima Shafira; ' Pranoto (Jurnal Privat Law, 2024)
AbstractThis article aims to find out the policies used by Bank BTN Solo Branch Office in providing credit relaxation for debtors during the COVID-19 pandemic. This research is empirical legal research and descriptive-analytical. The approach used in this study is qualitative approach. The type of data used is primary data derived from informant interviews at BTN Solo Branch Office as well as secondary data derived from the study of primary and secondary legal materials that use download and copy techniques and then collect, categorize and qualify primary and secondary legal materials as needed based on research objects. The technique of legal material analysis in this study uses sociological/teleological interpretation, systematic interpretation, and uses interactive analysis model. Legal problems arising in number 2 the points of regulation of POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of COVID-19 there is the word "can" which means not obliging banks to implement it, but giving the option to banks to implement or not relax credit based on these regulations in accordance with the policies of each bank. As a result, the policy was used by Bank BTN Solo Branch Office as a legal basis to provide credit relaxation for debtors affected by COVID-19.